PERAN GURU DALAM KEBERHASILAN PEMBELAJARAN SISWA TUNAGRAHITA DI SLBN BEKASI - Ira Restu Kurnia; Amelia Putri; Angghi Apryani; Bella Isnaeni; Deby Anatasya Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article aims to understand the importance of the teacher's role in the success of learning for students with intellectual disabilities. The writing of this article was conducted using qualitative methods. Data collection techniques were carried out through interviews, observations, and searching for various journal references related to the role of teachers in the learning success of students with intellectual disabilities. The research results indicate that the role of the teacher is very important in achieving learning success for students with intellectual disabilities. Learning that is tailored to the characteristics and needs of students. Teachers play a crucial role as determinants of success in education. Supporting factors for success include teacher competence, collaboration with parents, and the availability of facilities and infrastructure.